The Oxford handbook of Africa and economics - edited by Célestin Monga (Oxford Oxford University Press, 2015)
For a long time, economic research on Africa was not seen as a profitable venture intellectually or professionally-few researchers in top-ranked institutions around the world chose to become experts in the field. This was understandable: the reputation of Africa-centered economic research was not enhanced by the well-known limitations of economic data across the continent. Moreover, development economics itself was not always fashionable, and the broader discipline of economics has had its ups and downs, and has been undergoing a major identity crisis because it failed to predict the Great Recession.
Includes bibliographical references and indexes.
Keywords: Economics--Africa.